1990
DOI: 10.1210/endo-127-2-823
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inhibin Subunit Messenger Ribonucleic Acid Levels by Gonadotropins, Growth Factors, and Gonadotropin-Releasing Hormone in Cultured Rat Granulosa Cells*

Abstract: Cultured rat granulosa cells have provided a useful model to examine the hormonal regulation of inhibin secretion. In the present study we have used the cloned rat inhibin alpha- and beta A-subunit cDNAs to characterize the influences of gonadotropins, growth factors, and GnRH on inhibin subunit mRNA levels in granulosa cells obtained from immature estrogen-treated rats. Cells were cultured in medium with or without added hormones. Total RNA from cultured cells was extracted and hybridized with 32P-labeled inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 34 publications
5
33
1
Order By: Relevance
“…On the other hand, EGF decreases mRNA levels of inhibin in cultured rat granulosa cells [21]. Similar to the observation that the ET-2 secretion was inhibited by bFGF, the transcription of the inhibin gene was also repressed by bFGF [21]. Since the EGF and bFGF receptors have cytoplasmic tyrosine domains [22,23], signal transduetions triggered by tyrosine kinase may participate in the regulation of the transcriptions of ET-2 and inhibin genes by EGF, TGF-ct and bFGF.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, EGF decreases mRNA levels of inhibin in cultured rat granulosa cells [21]. Similar to the observation that the ET-2 secretion was inhibited by bFGF, the transcription of the inhibin gene was also repressed by bFGF [21]. Since the EGF and bFGF receptors have cytoplasmic tyrosine domains [22,23], signal transduetions triggered by tyrosine kinase may participate in the regulation of the transcriptions of ET-2 and inhibin genes by EGF, TGF-ct and bFGF.…”
Section: Discussionmentioning
confidence: 93%
“…In the granulosa cells, inhibin-α expression is stimulated by LH, FSH, cAMP analogs, and activin [2,16,37,41,46,47], whereas treatment with GnRH, protein kinase C activator, estradiol and estradiol with progesterone suppress FSH-stimulated inhibin-α expression [2,15,37,41]. Transforming growth factor (TGF)-α/epidermal growth factor (EGF) is thought to be a primary mitogen of granulosa cells [21], and the arachidonic acid metabolites by PGS, not the lipoxygenase metabolites, mediate the mitogenic effects of TGF-α/EGF, as demonstrated in the hen granulosa cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…Miyanaga et al, 1993 and references therein). The adenylate cyclase activator forskolin and a number of CAMP analogues have been shown to stimulate expression of a-inhibin subunit mRNA (Klaij et al, 1990;LaPolt et al, 1990;Najmabadi et al, 1993a). Pei et al (1991) identified a CRE element in the rat a-inhibin promoter that binds CREB and is responsive to forskolin in rat primary granulosa cells.…”
Section: Discussionmentioning
confidence: 99%